Time Travel - Richmond, Alasdair (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Philosophy of time travel is a fast-growing branch of philosophy, encompassing issues from metaphysics and epistemology through to the philosophy of science and philosophy of action. This Special Issue of Philosophies offers eight original contributions to the philosophy of time travel from expert practitioners in the field. Topics covered include causal loops, Grandfather Paradoxes, the dimensionality of time, attitudes to different times, foreknowledge, and the possibility of changing the past.